Firstly, let's factorise the polynomials:
1. x^2 + 2x + 1 = (x + 1)(x + 1) = (x +1)^2
2. x^2 + 3x + 2 = (x + 1)(x + 2)
3. x^2 + 6x + 5 = (x + 1)(x + 5)
Now, let's simplify the expression:
[(x + 1)^2 / (x + 1)(x + 2)] / [(x + 1)(x + 5) / (x + 2)(x - 2)]
We can cancel out common terms in the numerators and denominators:
= [(x + 1) / (x + 2)] / [(x + 1) / (x - 2)]
= (x + 1)(x - 2) / (x + 2)(x + 1)
= (x - 2) / (x + 2)
Therefore, the simplified expression is (x - 2) / (x + 2).
Factorise x squared plus 2x plus 1 on X squared plus 3x + 2 divided x squared plus 6x + 5 on X squared minus 4 and simplify
1 answer